PELAKSANAAN PENGALIHAN HAK MILIK ATAS BENDA MELALUI PERJANJIAN JUAL BELI MENURUT KUH PERDATA - Apriyanto, Hendra (LPPM STIH Awang Long, 2023)
This research aims to determine the implementation of the transfer of ownership rights to objects through a sale and purchase agreement according to the Civil Code. The aim of this research is to reveal the implementation of the transfer of property rights and what risks arise after the transfer of property rights occurs through a sale and purchase agreement. This type of normative research uses descriptive qualitative methods. The collection method uses library research (library study). How to analyze this research is descriptive analysis. Results obtained: Transfer of ownership rights over objects through a sale and purchase agreement which is carried out where the provisions of the law require that to obtain ownership rights based on delivery, two conditions must be met, namely the existence of a civil event to transfer ownership rights and the delivery, all of which must be made and carried out by a person who has the right to act freely with the property to be transferred. The risks in a sale and purchase agreement are that one party does not fulfill what has been agreed upon in the sale and purchase agreement. For delivery of goods, as long as the goods have not been delivered, the risk must still be borne by the seller, who remains the owner until the time the goods are legally handed over to the buyer or the risk of loss caused by an event (event) beyond the fault of either party.